2004
DOI: 10.1177/095440540421800504
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of drilling small and deep blind holes with an abrasive water jet

Abstract: In this paper an experimental study of drilling small and deep holes with a continuous abrasive water jet is presented. The abrasive water jet (AWJ) is a process that can be used for drilling a vast variety of materials. The main advantage of the AWJ is the absence of the heat-affected zone and its flexibility. Drilling tests were performed on different materials and the hole depth and diameter were observed at different machining times. It was found that when drilling different materials with a continuous jet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…Increment in the water pressure increases both the hole depth and the hole diameter. This result is consistent with the result reported by Orbanic and Junkar [14] in drilling blind hole using AWJ for some other materials. The authors presented an exponential relationship between the drilling depth and drilling time as below…”
Section: Awj Hole Drillingsupporting
confidence: 83%
See 1 more Smart Citation
“…Increment in the water pressure increases both the hole depth and the hole diameter. This result is consistent with the result reported by Orbanic and Junkar [14] in drilling blind hole using AWJ for some other materials. The authors presented an exponential relationship between the drilling depth and drilling time as below…”
Section: Awj Hole Drillingsupporting
confidence: 83%
“…Hlavac et al [13] investigated the AWJ trajectory curve inside the kerf and proposed a model that describes the curvature of the jet trajectory inside curve. Orbanic and Junkar [14] conducted an experimental study of drilling small and deep holes with a continuous AWJ and found that when drilling different materials with a continuous jet, the depth and diameter of the hole increase with a power function. However, titanium alloys were not included in their study.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (2) suggests a linear influence of jet time (t) on the material removal. Previous studies showed that the drilling depth increase is maximum after initiating the water jet (Akkurt, 2009;Bach et al, 2007;Orbanic and Junkar, 2004;Pandey and Panda, 2013;Matthujak et al, 2013), and, after the first few tenths of a second, increases almost linearly until a maximum depth is reached. The linear phase is therefore limited to a specific range of t. The same holds for P and D in their respective ranges.…”
Section: Discussionmentioning
confidence: 99%
“…For P , a minimal threshold needs to be met before bone material is removed, which lies between 30 and 45 MPa depending on the bone tissue and D (Honl et al, 2000a, b;den Dunnen et al, 2013a). The pressure range in which the pressure can be considered to have a linear influence is up to 120 MPa (Mohamed, 2004;Orbanic and Junkar, 2004). Thus, the volume of and velocity of the water is a good measure for the total volume of material removal, but only when no extreme values for D, t and P are used to achieve this volume and velocity of the water.…”
Section: Discussionmentioning
confidence: 99%
“…Dalam aplikasi proses pemesinan, Orbanic dan Junkar [4] melakukan studi ekperimental penggunaan partikel abrasive pada water jet untuk proses drilling lubang kecil dan dalam (small and deep hole). Percobaan proses drilling dilakukan pada beberapa material yang berbeda, sedangkan kedalaman dan diameter lubang diamati untuk waktu drilling yang berbeda.…”
Section: Pendahuluanunclassified